Implementasi Metode Backward Chaining untuk Mendiagnosa Penyakit pada Bayi Pasca Kelahiran - Alvin Supriyan; Arif Budimansyah Purba; Wawan Kusdiawan; Cepi Indra Grahana; Rani Amalia (Pusat riset dan Inovasi Nasional, 2024)
The critical period for the growth and development of infants can be referred to as a critical period. It is said that this critical period in infancy will be very detrimental to the environment around it and it is said that the future due to infancy is very short and cannot be repeated. Newborns are more susceptible to various diseases. Diseases in infants can be identified based on the symptoms that arise. This is caused by several factors including the lack of information about diseases in infants after birth that is known to the general public. Therefore, research is needed on diseases and symptoms that affect babies after birth. One alternative in order to find out the disease in the baby after birth can use an expert system. In building the system, the author uses the Backward Chaining method, uses the Waterfall system development method (SDLC) and the Object Oriented Approach (OOA). The result of this research is a web-based application that can later be accessed or used to make it easier for the public, especially parents of babies, to diagnose symptoms or diseases in babies after birth as early as possible.